Anomali Pernikahan: Determinasi Weton dalam Pernikahan Tradisi Jawa Persfektif Hukum Keluarga Islam - Willy Zulfan; Heri Firmansyah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The weton tradition is part of the local wisdom of Javanese society and continues to influence social practices, including determining marital compatibility. In practice, determining the birth date of a prospective partner through weton calculations is often used as a basis for proceeding with or canceling marriage plans. This phenomenon creates an anomaly when the weton tradition clashes with the principles of Islamic family law, which emphasize the pillars and requirements of marriage derived from the Quran and Hadith. This article aims to analyze the role of the weton tradition in marriage from the perspective of Islamic family law and examine the limits of tolerance between custom and sharia. The research method used is qualitative research with a normative-juridical and sociological approach. The results of the study indicate that the weton tradition is acceptable as long as it does not conflict with the principles of faith and is not used as a determining factor in determining the validity of a marriage.